Manajemen pendidikan kristiani dalam pembentukan karakter unggul - Christie Garry Mewengkang (KURIOS, 2023)
Educational management is closely related to creating a curriculum or managing classes in a learning process in educational institutions. The learning process that links Christian education with the formation of superior character has become a topic often repeated. However, connecting the management of Christian education with the appearance of excellent character is a discourse that needs to be considered in preparing the curriculum for Christian education. This article aims to show that the narrative of the formation of superior character is a necessity in Christian education. Using descriptive-constructive analysis methods, this research examines several previous literature related to Christian education. It produces an offer about building superior spirituality in Christian education to create excellent character. In conclusion, Christian education must be managed to develop the spirituality of exceptional Christian education.Â AbstrakManajemen pendidikan sangat berkaitan dengan pembuatan kurikulum atau mengelola kelas dalam sebuah proses belajar di lembaga pendidikan. Sejatinya, proses belajar yang mengaitkan pendidikan kristiani dengan pembentukan karakter unggul telah menjadi bahasan yang kerap diulang-ulang; namun, bagaimana mengaitkan manajemen pendidikan kristiani dengan pembentukan karakter yang unggul merupakan sebuah diskursus yang perlu dipertimbangkan dalam menyusun kurikulum di pendidikan Kristen. Artikel ini bertujuan untuk menunjukkan bahwa narasi pembentukan karakter unggul menjadi niscaya dalam pendidikan kristiani. Dengan menggunakan metode analisis deksriptif-konstruktif, penelitian ini mengkaji beberapa literatur terdahulu terkait pendidikan kristiani, dan menghasilkan tawaran tentang membangun spiritualitas unggul dalam pendidikan kristiani sebagai cara membangun karakter unggul. Kesimpulannya, pendidikan kristiani perlu dikelola untuk dapat membangun spiritualitas pendidikan kristiani yang unggul. Â